Construction of six new luminescent Ln(iii)–Zn(ii) heterometallic coordination polymers based on heterometallic secondary building units. Issue 44 (28th October 2016) - Zheng, Sheng-Run; Tan, Jing-Bo; Cai, Song-Liang; Fan, Jun; Zhang, Wei-Guang
Abstract : Six new Ln(iii )–Zn(ii ) heterometallic coordination polymers with two types of metal ions and two types of organic carboxylate ligands based on well-defined heterometallic SBUs were explored. Abstract : Six new d–f heterometallic Ln(iii )–Zn(ii ) coordination polymers (CPs), namely, [EuZn(NIPH)1.5 (INC)(H2 O)(OH)]·0.5H2 O n (1 ), [LnZn(NIPH)2 (INC)(H2 O)] n [Ln = Eu (2 ), Tb (3 )], [EuZn2 (NIPH)2.5 (INC)2 ] n (4 ) and [LnZn(NIPH)2 (NC)(H2 O)] n [Ln = Eu (5 ), Tb (6 )] [H2 NIPH = 5-nitroisophthalate, HINC = isonicotinate, and HNC = nicotinate], were obtained under hydrothermal conditions. All the compounds are based on well-defined heterometallic secondary building units (SBUs). Compound1 is a 3D network withpcu topology, which was generated from tetragonal tetranuclear heterometallic [Eu2 Zn2 (NIPH)4 (INC)2 (OH)2 ] SBUs connected by NIPH 2− and INC − ligands. Compounds2 and3 are isostructural and exhibit 3D heterometallic frameworks withbcu topology constructed by the linkage of 2D layers containing linear tetranuclear heterometallic [Eu2 Zn2 (NIPH)6 (INC)2 ] SBUs and INC − anions. Compound4 possesses 7-connected 3D frameworks with the Schläfli symbol of (3 3 ·4 11 ·5 6 ·6) constructed by the interconnection of linear trinuclear heterometallic [EuZn2 (NIPH)4 (INC)4 ] SBUs, NIPH 2− ligands and INC − anions. In compounds5 and6, 3D networks are formed through the linkage among linear tetranuclear [Ln2 Zn2 (NIPH)8 (NC)2 ] SBUs, NIPH 2− ligands and NC − anions. All the compounds represent examples of 3D lanthanide–transition heterometallic–organic coordination polymers with two types of metal ions and two organic carboxylates. Furthermore, their solid-state fluorescence properties have been investigated at room temperature.